For the publication of the manuscript of the Abkhazian language dictionary: Teimuraz Gvantseladze, The First Dictionary of the Abkhazian Language", 1827 - Tabidze, Manana; Shavkhelishvili, Bela (Actual Problems of Kartvelology, 2013)
We consider the "Abkhazian Dictionary" by Vladimir Romanov ("Абазинской словарь"); this is a Russian-Abkhazian dictionary, the text of which was prepared for publication, Abkhazian dialectal forms were restored, and a preface and research were added by Professor Teimuraz Gvantseladze (The First Dictionary of the Abkhazian Language. Vladimir Romanov, Abaza Dictionary. National Library of the Parliament of Georgia, Institute of Abkhazian Language and Culture of Sukhumi State University, Tbilisi, 2013, 205 p.). In our pragmatic era, the contribution of a scientist is less appreciated; moreover, some people think that great work can only be done for great pay... Against this background, it may seem strange to some that Professor Teimuraz Gvantseladze's tireless work in identifying such manuscripts and forgotten printed materials of the Abkhazian language, restoring their forms, compiling them into an electronic version, In the direction of research and publication, the names of those Abkhazian, Russian, and Georgian figures who once played an important role in the fate of these texts, but who are now remembered less (or not at all) by modernity, are written in capital letters, while the discoverer, restorer, reviver, dedicater to modernity, and bring them into scientific circulation are modestly mentioned in the title of the book, below, in small font (“The text of the dictionary was prepared for publication, Abkhazian dialectal forms were restored, and a preface and research were added by Professor Teimuraz Gvantseladze”); The Abkhazian words and phrases given in the dictionary belong to the Bzyb / Bzipi dialect or a speech close to it, and accordingly, by providing the reader with this dictionary, Teimuraz Gvantseladze introduces Abkhazologists, and first of all, the Abkhazians themselves, to the Bzyb / Bzipi dialect of the second decade of the nineteenth century. The importance of this material is increased by the fact that after the 1960s of the nineteenth century, the Abkhazian inhabitants of Sukhumi-Kale and its surrounding area were expelled from this region by Russia, which is why the forms recorded in the dictionary on this territory are no longer represented today. When we talk about the difficulties of establishing the text, we have in mind the fact that “to convey Abkhazian words in the dictionary, the compiler uses almost all the letters of the Russian alphabet (Cyrillic) without any additional graphic elements (diacritical marks, transcription symbols, etc.), which, naturally, leads to many inaccuracies in the conveyance of Abkhazian linguistic material, especially since the Abkhazian language and its Bzyb / Bzipi dialect contain twice as many phonemes as the Russian language. Errors also occur because the author’s ear was clearly not accustomed to Abkhazian speech and had difficulty correctly perceiving the phonemes of this language” (T. Gvantseladze, p. 173). It should be noted that one of the most important parts of T. Gvantseladze’s research is the phonetic analysis, because here not only the description of lexical data is presented, but also a deep study of the dialects of the Abkhazian language is given in this regard; during the analysis, the author also discusses the errors that were caused (and still are) by the recording of Iberian-Caucasian material in Cyrillic, and also the fact that the “Russian-speaking listener” who does not know Abkhazian “does not understand” many sounds (there is something symbolic in this “not understanding”); the researcher dwells in detail on Romanov’s perception of vowels and consonants, tries to explain the reasons for the different recording of the same phoneme, and offers us a reconstructed phonemic system of Abkhazian speech, widespread in the speech of the Abkhazians living in Sukhumi-Kale and the surrounding area in the 1920s. Here, as far as possible, the original variants of Abkhazian words have been determined, which have been reconstructed taking into account the data of the Bzyb / Bzipi dialect. In the study, lexical forms are specifically characterized in terms of the transmission of specific consonant phonemes common to Abkhaz.